ANALISIS DALAM PENYUSUNAN RANCANGAN RETRIBUSI PEMAKAIAN KEKAYAAN DAERAH DI KABUPATEN TULANG BAWANG - Nandang Nandang (Rekayasa : Jurnal Ilmiah Fakultas Teknik Universitas Lampung, 2009)
The implementation of the region autonomy had been done since 2001, it gave the authority andthe freedom to the district government of Tulang Bawang in developing the economic potency andthe financial resources in Tulang Bawang.To reach the purpose, the district government should do the analysis of the district economicpotency. It is important to be done because the pure income potency (PAD) from the district isvery low (about 10 %) from the budget in this year (APBD). While the fund from the centralgovernment especially it from the general allocation fund, the biggest fund is used to pay thedistrict officials.It motivates the district government to dig the economic potency in the improvement of thefinancial potency. The way is the optimalization of PAD in the use of the district affluence bymaking the retribution in Tulang Bawang.